1995
DOI: 10.1128/iai.63.9.3467-3472.1995
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Borrelia burgdorferi to the proteoglycan decorin

Abstract: Lyme disease is a tick-borne infection that can develop into a chronic, multisystemic disorder. The causative agent, Borrelia burgdorferi, is initially deposited by the tick into the host dermis, where it associates with collagen fibers, replicates, and eventually disseminates to other tissues. We have examined the adherence of the spirochete to different components of the collagen fiber and demonstrated that decorin, a proteoglycan which decorates collagen fibers, can support the attachment of B. burgdorferi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(137 citation statements)
references
References 23 publications
1
134
0
2
Order By: Relevance
“…Of course, additional adhesins participate in the attachment of pathogenic bacteria to mammalian cells and tissues. B. burgdorferi, for example, expresses the lipoprotein adhesins decorin-binding protein (Guo et al, 1995;1998) and fibronectin-binding protein (Probert and Johnson, 1998). A candidate B. burgdorferi ligand for heparan and dermatan sulphate has been identified recently (N. Parveen and J. M. Leong, unpublished). B. burgdorferi p66 does not contain any consensus integrin recognition motifs, but the same is true of invasin, the Yersinia protein that binds with high affinity to several ␤ 1 -chain integrins Leong et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, additional adhesins participate in the attachment of pathogenic bacteria to mammalian cells and tissues. B. burgdorferi, for example, expresses the lipoprotein adhesins decorin-binding protein (Guo et al, 1995;1998) and fibronectin-binding protein (Probert and Johnson, 1998). A candidate B. burgdorferi ligand for heparan and dermatan sulphate has been identified recently (N. Parveen and J. M. Leong, unpublished). B. burgdorferi p66 does not contain any consensus integrin recognition motifs, but the same is true of invasin, the Yersinia protein that binds with high affinity to several ␤ 1 -chain integrins Leong et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…We used a microtitre well attachment assay to study the adherence of B. burgdorferi to decorin. Initial experiments showed that strain N40 (Guo et al, 1995) could adhere to decorin-coated microtitre wells. The effects of purified, recombinant Dbps or OspC on bacterial adherence were examined in experiments in which decorin-coated wells were preincubated with increasing concentrations of recombinant Borrelia proteins for 1 h before whole B. burgdorferi cells were added.…”
Section: Dbpa Can Inhibit the Attachment Of B Burgdorferi To Decorinmentioning
confidence: 99%
“…The following shows the changes made to the established attachment assay of Guo et al (1995). Microtitre plates were coated overnight at 4°C with 100 lL of a 0.5, 1 and 10 lg mL À1 solution of human fibronectin (R&D Systems).…”
Section: Attachment Of Leptospira To Fibronectinmentioning
confidence: 99%